2021
DOI: 10.47059/revistageintec.v11i2.1788
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure and Commercial Banks Performance: An Empirical Study from Emerging Markets

Abstract: The current study seeks to investigate the relationship between ownership structure concentrations and commercial banks financial performance in one of emerging market (Bahrain). The current study employed panel regression analysis from 2015-2019 estimate the relationships between dependent and independent variables. The findings revealed that there is a positive impact of family, government and institutional ownership on financial performance measured by return on equity. Meanwhile, there is negative impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
6
3
Order By: Relevance
“…The study finding supports the work of authors in [68,69] who established a negative association between institutional ownership and financial performance. This finding contradicted the work of [51,63,[65][66][67] who found a positive relationship between institutional ownership and firms' financial performance. In addition, the finding of this study contradicted the work of [3,59] who observed that high firm's financial performance is deemed to be associated with institutional ownership which provides high quality management and improved corporate governance in the firms.…”
Section: Ownership Structures and Return On Assetscontrasting
confidence: 97%
See 1 more Smart Citation
“…The study finding supports the work of authors in [68,69] who established a negative association between institutional ownership and financial performance. This finding contradicted the work of [51,63,[65][66][67] who found a positive relationship between institutional ownership and firms' financial performance. In addition, the finding of this study contradicted the work of [3,59] who observed that high firm's financial performance is deemed to be associated with institutional ownership which provides high quality management and improved corporate governance in the firms.…”
Section: Ownership Structures and Return On Assetscontrasting
confidence: 97%
“…However, previous empirical studies found mixed conclusions. Some studies established a positive relationship between institutional ownership and firms' financial performance [51,[62][63][64][65][66][67]. Other studies observed a negative association between institutional ownership and financial performance [68,69].…”
Section: Institutional Ownershipmentioning
confidence: 99%
“…The study finding supports the work of authors in [68,69] who established a negative association between institutional ownership and financial performance. This finding contradicted the work of [51,63,[65][66][67] who found a positive relationship between institutional ownership and firms' financial performance. In addition, the finding of this study contradicted the work of [3,59] who observed that high firm's financial performance is deemed to be associated with institutional ownership which provides high quality management and improved corporate governance in the firms.…”
Section: Ownership Structures and Return On Assetscontrasting
confidence: 99%
“…However, previous empirical studies found mixed conclusions. Some studies established a positive relationship between institutional ownership and firms' financial performance [51,[62][63][64][65][66][67]. Other studies observed a negative association between institutional ownership and financial performance [68,69].…”
Section: Institutional Ownershipmentioning
confidence: 99%
“…Study (Oudat et al, 2021) sought to verify the relationship between the ownership structure and the financial performance of commercial banks, and found that there is a positive impact of government and family ownership on financial performance as measured by return on property rights study (Akin and Ozsoy, 2021) showed that the profitability of state-owned Islamic banks is slightly higher than that of private Islamic banks, and a chronology analysis of this study shows that state-owned Islamic banks performed at least as well as private banks.The results of this study, by knowing the relationship between the ownership structure and the financial performance of Islamic banks, indicated that joint efforts between family and state investors are beneficial to the bank's performance.…”
Section: State Ownership and Financial Performancementioning
confidence: 99%